2014
DOI: 10.1017/s175173111300236x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of livestock production system and concentrate level on carcass traits and meat quality of foals slaughtered at 18 months of age

Abstract: This trial was conducted to study the effect of livestock production system (freedom extensive system (FES) v. semi extensive system (SES)) and amount of finishing feed (1.5 v. 3.0 kg of commercial feed) in SES on carcass characteristics, meat quality and nutritional value of meat foal slaughtered at 18 months of age. For this study, a total of 49 foals (21 from FES and 28 from SES) were used. The obtained results showed that SES had a positive influence on carcass characteristic because these foals showed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
32
12
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(76 citation statements)
references
References 29 publications
29
32
12
3
Order By: Relevance
“…The CCI (1.38 and 1.48 for animals from the 8-and 11-m groups, respectively) and hindlimb compactness index (HCI; 3.70 and 3.68 for animals from the 8-and 11-m groups, respectively) also showed no significant differences with an increase in slaughter age. As expected, our results agree with those of Franco et al (2013) (1.44 and 3.68 for CCI and HCI, respectively) and Lorenzo et al (2014a) (1.42 and 3.86 for CCI and HCI, respectively) in GM × HB foals finishing with 3 kg of commercial fodder and slaughtered between 15 and 18 months of age.…”
Section: Carcass Characteristicssupporting
confidence: 91%
See 4 more Smart Citations
“…The CCI (1.38 and 1.48 for animals from the 8-and 11-m groups, respectively) and hindlimb compactness index (HCI; 3.70 and 3.68 for animals from the 8-and 11-m groups, respectively) also showed no significant differences with an increase in slaughter age. As expected, our results agree with those of Franco et al (2013) (1.44 and 3.68 for CCI and HCI, respectively) and Lorenzo et al (2014a) (1.42 and 3.86 for CCI and HCI, respectively) in GM × HB foals finishing with 3 kg of commercial fodder and slaughtered between 15 and 18 months of age.…”
Section: Carcass Characteristicssupporting
confidence: 91%
“…Therefore, as expected, the differences in LW and CW could be due to the fact that animals from the 11-m group were 3 months older than the animals from the 8-m group. The results obtained in the present study are similar those reported by Franco et al (2013) and Lorenzo et al (2014a) in foals receiving a finishing diet and slaughtered between 15 and 18 months of age (258 to 287 kg for LW and 132.8 to 152.2 kg for CW). However, Lorenzo et al (2013a) reported lower values of LW (184 to 194 kg) and CW (87.5 to 93.3 kg) in foals raised in an extensive production system in freedom regimen and slaughtered at 18 months of age.…”
Section: Carcass Characteristicssupporting
confidence: 91%
See 3 more Smart Citations